Incidence and Risk Factors of Sacroiliac Joint Pain Following Lumbar Surgery with and without Fusion in Patients with Spinal Stenosis and Low-Grade Degenerative Spondylolisthesis: A Nonrandomized Clinical Trial - Javadi, Toufigh Mohaddes; Moghadam, Navid; Bagherzadeh, Sadegh; Kordi, Ramin; Kim, Dustin; Roohollahi, Faramarz; Moosavi, Mersad; Jouibari, Morteza Faghih; Shafizadeh, Milad; Jafarieh, Arash; Rostami, Marzieh; Ataei, Hosseinali; Jafari, Mohammad; Rostami, Mohsen (Asian Journal of Neurosurgery, 2025)
Failed back surgery syndrome affects 10 to 46% of lumbar spine surgery patients, often resulting in persistent pain and functional impairment. Sacroiliac joint pain (SIJP) is a significant contributor, particularly following spinal fusion. This study aimed to assess SIJP incidence following lumbar surgery with and without fusion, and identify risk factors for sacroiliac joint syndrome (SIJS).This prospective, nonrandomized clinical trial included 102 patients undergoing lumbar decompression alone (Dec group, n = 50) or decompression with fusion (DecPlus group, n = 52) at two university hospitals. Patients with persistent postoperative pain were assessed for SIJS using clinical provocative tests and fluoroscopy-guided sacroiliac joint blocks. Primary outcomes included SIJP incidence, visual analog scale (VAS) for pain, Oswestry Disability Index (ODI) for disability, and Short-Form (SF)-36 Health Survey for quality of life. Patients were followed for 3 months postoperatively.SIJP was diagnosed in 36.3% of patients, with significantly higher incidence in the DecPlus group (50%) compared with the Dec group (22%) (p < 0.01). Pain scores (VAS) improved significantly in both groups, but ODI and SF-36 scores showed greater improvement in the Dec group (p < 0.01). SIJP has a significant relation with the upper instrumented vertebra (UIV) and length of fusion; however, extension of fusion to S1 does not significantly increase the SIJP. There was no significant association between SIJP and smoking, body mass index, or other comorbidities.Based on our study, lumbar instrumented posterolateral fusion, compared with decompression without fusion, should be considered a risk factor for SIJP. In patients with instrumented fusion, the UIV and the length of fusion are related to SIJP; however, extending fusion to S1 does not significantly affect SIJP incidence.
Keywords: decompression; fusion; sacroiliac joint pain; failed back surgery syndrome